The equality effect: Improving life for everyone - Dorling, D (New Internationalist, 2017)
Greater economic equality is beneficial to all people in all societies, both for the rich, the poor and the rest. The equality effect is demonstrable both nationally and internationally. These claims are contentious because their truth has only become evident recently, and because these findings contradict dominate views of many of the elite.